Human biology for AS - Jones, Mary, 1950-; Jones, Geoff (Cambridge ; New York : Cambridge University Press, 2004)
Human Biology provides full coverage of the specification from OCR first introduced in September 2003. It carries an endorsement from the awarding body and is written by Mary Jones and Geoff Jones who are the authors of numerous successful textbooks for biology courses.
unit 1; the blood; 1. observing the blood; 2. investigating blood chemistry; 3. blood clotting; the heart; 4. heart disease and cardiac arrest; 5. monitoring heart function; 6. maintaining a healthy heart; the lungs; 7. lung function and lung disease; unit 2; the developing cell; 8. stem cells and DNA; 9. detecting and treating cancer; the developing individual; 10. investigating foetal development; 11. investigating infant development; infectious disease; 12. preventing infectious disease; 13. the future of infectious disease control
Includes index.
Keywords: Human biology